PENGARUH BERKUMUR AIR REBUSAN DAUN SALAM KERING (EUGENIA POLYANTHA) TERHADAP PH SALIVA - Bedjo Santoso; Irmanita Wiradona; Noor Afifah (Jurnal Kesehatan Gigi, 2015)
TITLEThe effect of rinse using water stew of dry bay leaf (Eugenia polyantha) toward pH salivaABSTRACT Caries is the main couse of disease of the oral cavity caused by saliva. Salivary pH acidic and  susceptible to caries. Saliva is a buffer system to maintain optimum pH in the oral cavity. To keep salivary pH balance,can do prevented by chemically and mechanically. Chemically prevention can do rising mouth with bay leaves dried because it contain essential oil 0.17 % which can stimulate secretion of saliva. Increased secretion of saliva can increasing buffer on saliva so it can in salivaincreas and tend to be alkaline. Aim to know the effect of rising mouth with water stewbay leaves dried ( eugenia polyantha ) on salivary to pH to the students of Dental Health  Departement of Semarang .Research is quantitative descriptive. Research method is quasi exsperimental with cross sectional approach. Research design one group pretest – posttest. Collection of samples in this research using by using 20 samples,The test result of paired t -test showed 0.000 0.05 that there was influence of rising mouth with water stewbay leaves dried on salivary pH. It can be concluded that rising mouth with water stew bay leaves dried can cause changes in the pH of saliva.